Analysis of the content of heavy metal ions in the coastal zones of the northern part of the Apsheron peninsula - Aliyeva, N.T.; Sadigov, R.A.; Mamedova, R.I.; Ibadova, S.Y. (Fundamental and Experimental Biology, 2023)
The article is devoted to studies of heavy metal pollution of the soil cover of the coastal zones of the northern part of the Apsheron Peninsula. Pollution of the coastal zones of the Caspian Sea, serving to a greater extent as a recreational area for the population, by toxic substances is of great concern and to solve this problem, periodic studies of these zones for the presence of heavy metals are necessary. For the first time, a comparative analysis of the content of heavy metals in different areas (Buzovna, Sumgait, Novkhany) of the northern part of the Apsheron peninsula was carried out and the presumable causes of their accumulation were outlined. The researched soils in the northwestern and northeastern part of the peninsula were grouped according to the degree of concentration of heavy metals depending on the depth of the researched soils. Zinc (77.0 mg/kg, at 0–16 cm depth, transect №03), copper, and cadmium (88 mg/kg and 0.36 mg/kg at 0–20 cm depth, transect №05) had the highest concentrations relative to other trace elements. Concentrations of zinc and copper in the northwestern direction of the peninsula increase by 1.5 and 3–3.5 times, respectively, as compared with the generally accepted norms. Average content of heavy metals, especially Ni, Cd, Pb in flooded soils at the depth of 0–100 cm increased 2.7 times on average as a result of coastal flooding by waters of Caspian Sea. The value of total heavy metals reaches a maximum in the northwestern direction.